PENGARUH PEMBERIAN EDUKASI KEAMANAN PANGAN TERHADAP PERUBAHAN PENGETAHUAN DAN SIKAP PEDAGANG PENYETAN DI WILAYAH TEMBALANG - Dwi Kurnia Yulia Ratnasari; M. Zen Rahfiludin; Dina Rahayuning Pangestuti (Jurnal Kesehatan Masyarakat (Undip), 2018)
The high incidences of food poisoning and foodborne disease can be attributable to someone’s low knowledge of food safety, which leads to the selection of the wrong attitude. Low levels of knowledges and attitudes about food safety will cause someone has a bad practice of food safety. Food safety education is done by extension method using module as media because two-way communication can be more helpful to increase knowledge and behavior and use of module as educational media have some advantages that is material which poured in module more complete, clear and educative. The aim of this research is to analyze the influence of education with food safety module on knowledge and attitude changes on penyetan traders in Tembalang Region Semarang City. Research type is Quasi Experimental with One group pre test-post test design. Sampling technique using purposive sampling with 58 people of samples. Different test using  Wilcoxon Signed Rank test. There is an average number of respondent's knowledge before and after intervention (p = 0.0001). There is difference of mean of attitude of respondents before and after intervention (p = 0.0001).